Economic viability of dairy heifer production on pasture in crop-livestock integration system - Silva, Hernani Alves da; Moraes, Anibal de; Carvalho, Paulo César de Faccio; Fonseca, Adriel Ferreira da; Guimarães, Vânia Di Addario; Monteiro, Alda Lúcia Gomes; Lang, Claudete Reisdorfer (Pesquisa Agropecuaria Brasileira, 2012)
<span lang="EN-US" style="line-height: 115%; font-family: "TimesNewRomanPSMT","serif"; font-size: 10pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: TimesNewRomanPSMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">The objective of this work was to evaluate the profitability of the integrated crop-livestock (ICL) system in comparison to the cultivation of winter cereals and cover plants for soybean and maize cropped under no‑<span lang="EN-US" style="line-height: 115%; font-family: "TimesNewRomanPSMT","serif"; font-size: 10pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: TimesNewRomanPSMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">tillage in the summer. The following were compared: simulated data from a conventional agricultural system with production of maize and soybean grains in the summer and cultivation of wheat and ground cover plants in the winter; and data from a published work in which combinations of pastures (diversified or pure) and animal categories (light or heavy) were evaluated in a system with the production of maize and soybean in the summer and grazing during the winter. Economic analysis was carried out based on previous experimental results and simulated for a 100‑<span lang="EN-US" style="line-height: 115%; font-family: "TimesNewRomanPSMT","serif"; font-size: 10pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: TimesNewRomanPSMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">ha property. ICL with rearing of dairy heifers in winter annual grazing, as a replacement to winter cereal crops and ground cover crops for no-tillage, is the most profitable alternative for producers.